"Glass fairies" and "bone children": Adolescents and young adults with anorexia nervosa show positive reactions towards extremely emaciated body pictures measured by the startle reflex paradigm. (11th November 2013) - Reichel, Valeska A.; Schneider, Nora; Grünewald, Barbara; Kienast, Thorsten; Pfeiffer, Ernst; Lehmkuhl, Ulrike; Korte, Alexander
Abstract In this study, we investigated the emotional processing of extremely emaciated body cues in adolescents and young adults with (n = 36) and without (n = 36) anorexia nervosa (AN), introducing a new picture type, which was taken from websites that promote extreme thinness and is targeted specifically at adolescents interested in extreme thinness. A startle reflex paradigm was used for implicit reactions, while a self‐assessment instrument was used for subjective responses. We found a significant group difference with a startle inhibition (appetitive response) among the patients and a startle potentiation (aversive response) among the controls, whereas no such difference for subjective measures was found. The results are in contrast to previous studies, which proposed a general failure to activate the appetitive motivational system in AN, but in keeping with findings from other addictions, where the same response pattern has been found. Implications for prevention and therapy are discussed.